MEMBANGUN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA PONDOK PESANTREN SALAFIYAH AL-BAQIYATUSSA’DIYYAH TEMBILAHAN - Abi Burrahman (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2017)
Information system are running at the Islamic School Salafiyah Al-Baqiyatussa’diyyah Tembilahan, that the academic data processing still using a simple computerized system. Althought it is supported by the computer but only use standard office (Microsoft Office Excel and Word) that allows a lot of errors in the processing of academic data, and the cause of academic services providedby the Islamic school Salafiyah Al-Baqiyatussa’diyyah Tembilahan to be less efficient, and the resulting difficulty in data search and seize a relatively long time in the making of the report. To assist in solving these problem is need fr a new academic information system so that any work involving the processing of data can be reduced and the error rate can provide satisfactory services of the user the system. On the design of academic information system is ilustrated in the diagram Unified Modelling Language (UML).Keyword : Akademik, Sistem Informasi, SDLC, UML.